Proposed new design retail for Karyaneka at The Gardens, Midvalley / Khiflani Jailan - Jailan, Khiflani (Faculty of Architecture, Planning and Surveying, 2008)
The final project of Interior Design for diploma is the manifestation to students’ understanding on process aspects of interior design that has been studied from the basic to presentation level of design proposal. The chosen product for this project is retail for KARYANEKA, Malaysia’s well known handicraft and souvenir centre. The proposed site is situated at Lot 221 and 222, The Gardens, 55000 Midvalley. The purpose of this project is to introduce the products of KARYANEKA. In running this project, the most important of the retail is to make varieties of design for the display items for the products. It is also to instill interest of people to buy or to have products of KARYANEKA. The research method for this project is based on observation of KARYANEKA headquarters and showroom at Jalan Conlay, Kuala Lumpur. The advantages of having this KARYANEKA’s retail project, is to give a new impression of art and craft of Malaysia and the origin of it and to deliver imformation to the new generation. Every Malaysian should have known about this product, in conclusion, the new design retail that will be run should have the characteristics and customers’ needs besides the suitable concept should be shown.